Clinical factors and dopamine transporter availability for the prediction of outcomes after globus pallidus deep brain stimulation in Parkinson’s disease - Seung Hyun Lee; Mina Kim; Jooyoung Lee; Jae-Woo Kim; Mi Sun Kim; Sungyang Jo; Sang Ryong Jeon; Sun Ju Chung (Scientific Reports, 2022)
Abstract We aimed to investigate the predictive value of preoperative clinical factors and dopamine transporter imaging for outcomes after globus pallidus interna (GPi) deep brain stimulation (DBS) in patients with advanced Parkinson’s disease (PD). Thirty-one patients with PD who received bilateral GPi DBS were included. The patients underwent preoperative [18F] FP-CIT positron emission tomography before DBS surgery. The Unified Parkinson’s Disease Rating Scale (UPDRS) were used to assess outcomes 12 months after DBS. Univariate and multivariate linear regression analysis were performed to investigate the association between clinical variables including sex, age at onset of PD, disease duration, cognitive status, preoperative motor severity, levodopa responsiveness, daily dose of dopaminergic medication, and dopamine transporter availability in the striatum and outcomes after GPi DBS. Younger age at onset of PD was associated with greater DBS motor responsiveness and lower postoperative UPDRS III score. Greater levodopa responsiveness, lower preoperative UPDRS III score and lower striatal dopamine transporter availability were associated with lower postoperative UPDRS III score. Younger age at onset was also associated with greater decrease in UPDRS IV score and dyskinesia score after GPi DBS. Our results provide useful information to select DBS candidates and predict therapeutic outcomes after GPi DBS in advanced PD.